2020
DOI: 10.21203/rs.3.rs-75485/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting Language Recovery in Post-Stroke Aphasia using Behavior and Functional MRI

Abstract: Background: Language outcomes after speech and language therapy in post-stroke aphasia are challenging to predict. This study examines behavioral language measures and resting state fMRI (rsfMRI) as prognostics for response to language therapy. Methods: Seventy patients with chronic aphasia were recruited and treated for one of three deficits: anomia, agrammatism, or dysgraphia. Treatment effect was measured by performance on a treatment-specific language measure, assessed before and after three months of lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Previous studies from our group on a subset of these data showed that brain function data, 15,36 brain structure information, 9,14 and language and cognitive performance 11,36 independently predict treatment-related outcomes. This study is the first, to our knowledge, to investigate the cumulative importance of patient-related information using a comprehensive data set including behavioral, demographic, and multimodal neuroimaging information to predict rehabilitation-induced language recovery in individuals with chronic poststroke aphasia.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies from our group on a subset of these data showed that brain function data, 15,36 brain structure information, 9,14 and language and cognitive performance 11,36 independently predict treatment-related outcomes. This study is the first, to our knowledge, to investigate the cumulative importance of patient-related information using a comprehensive data set including behavioral, demographic, and multimodal neuroimaging information to predict rehabilitation-induced language recovery in individuals with chronic poststroke aphasia.…”
Section: Discussionmentioning
confidence: 98%
“…Imaging protocols were harmonized across sites to ensure similar quality and timing and these protocols have been reported in previous papers. 35–37 Structural imaging included a T1-weighted sagittal sequence (voxel size=1×1×1 mm 3 ), and a high-resolution whole-brain cardiac-gated diffusion-weighted imaging sequence (voxel size=1.983×1.983×2.000 mm 3 , 72 interleaved slices with 60 gradient directions and 10 nondiffusion weighted ( b =0) volumes, b value=1500 s/mm 2 ). Whole-brain functional images were collected using a gradient-echo T2*-weighted sequence (voxel size=1.72×1.72×3 mm 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recent literature has developed strategies to combine different data modalities (anatomical, functional, behavior, etc.) of stroke patients ( Iorga et al, 2021 , Kristinsson et al, 2021 , Pustina et al, 2017 ). While this study does not include anatomical information of the patients, future multimodal studies could adapt the presented methods to include the structural constraints of each individual subject.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews agree that lesion-related factors, such as initial aphasia severity, lesion size, and affected structures (3)(4)(5) are more relevant predictors of outcomes than demographic factors (e.g., age, education). Along with improvement of neuroimaging techniques and statistical approaches (6)(7)(8)(9), modeling of PSA recovery has become an important goal in aphasia research. Two aspects of recovery have increasingly received attention: how to measure the recovery phenomenon and what brain regions and structures are associated with this recovery.…”
Section: Introductionmentioning
confidence: 99%